Two‐Color Glycan Labeling of Live Cells by a Combination of Diels–Alder and Click Chemistry1. Issue 15 (6th March 2013) - Niederwieser, Andrea; Späte, Anne‐Katrin; Nguyen, Long Duc; Jüngst, Christian; Reutter, Werner; Wittmann, Valentin
<x xml:space="preserve">Abstract</x> One is not enough: Terminal alkenes are used as chemical reporters and ligation partners for 1, 2, 4, 5‐tetrazines in a Diels–Alder reaction with inverse electron demand (DARinv). Combination with strain‐promoted azide–alkyne cycloaddition (SPAAC) allows the visualization of two different glycan structures in one experiment.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>